Integration of logistic systems into regional transport services using road cargo transport - Cempirek, V.; Seidlova, A.; Siroky, J.; Nachtigall, P.; Kampf, R. (Transactions on Transport Sciences, 2008)
The paper deals in the analytic part with problems of taxes and charges paid by users of road transport. Our team found that those payments are lower than for railroad transport, so that toll system implementation can't incite movement of transport from road to railroad. New partnerships between road and railroad companies can be set up here. This will lead to intermodal systems with savings on tolls, namely domestically, but in international transport. The proposal part of intermodal system deals with systems like Mobiler and Cargo Domino or Modalohr and Cargo Beamer. The conclusion is a better regional service technology and costs savings thanks to the cooperation of road and railroad transport. Intermodal systems are destined for a minimal hauling distance of 600 km with accompanied or unaccompanied transport.
Keywords: Cargo system; logistic system; road; rail; transport.